A Study to Explore the Role of IDH1 (R132) Mutation on Imatinib Toxicity and Effect of ABCG2/OCT1 Expression on N-Desmethyl Imatinib Plasma Level in Egyptian Chronic Myeloid Leukemia Patients - Sabri, Alaa; Omran, Mervat M.; Azim, S.Abdel; Abdelfattah, Raafat; Allam, Rasha Mahmoud; Shouman, Samia A. (Drug Research, 2023)
Imatinib mesylate (IM) is the gold standard for treatment of Chronic Myeloid Leukemia (CML). This study aimed to gain more knowledge of the altered PK, pharmacogenetic factors, and gene expression leading to variable IM levels. Fifty patients with chronic phase-CML were enrolled in this study and divided as 25 responders and 25 non-responders (patients are directly recruited after response assessment). HPLC/MS/MS was used to determine trough and peak concentration of imatinib and N-desmethyl imatinib in the blood. PCR-RFLP technique was used to detect IDH1 gene mutation (R132). The median value of IM trough level was significantly higher, the P/T ratio was significantly lower and the α-1-acid glycoprotein (AGP) was significantly higher among responders compared to non-responders (P=0.007, 0.009 and 0.048, respectively). Higher N-desmethyl imatinib peak plasma concentration was observed with low mRNA expression of ABCG2 and OCT1 (P=0.01 and 0.037, respectively). IDH1 R132 gene mutation was associated with a significant increase in toxicities (P=0.028). In conclusion, IM trough level, P/T ratio and AGP was significantly higher in responders. In addition, ABCG2 and OCT1 gene expression may affect the interindividual PK variation. Although a prospective study with a larger patient population is necessary to validate these findings. IDH1 mutation is a predictor of increased toxicity with IM treatment.
Keywords: CML; Imatinib; N-desmethyl imatinib; mutation; gene expression; OCT1; IDH1